Improving the homogeneity of diffraction based colours by fabricating periodic patterns with gradient spatial period using Direct Laser Interference Patterning - Bogdan Voisiat (Nature Portfolio, 2019)
Abstract This study focuses on the development of a strategy to produce periodic structures with a variable spatial period for increasing the homogeneity of structural colours by means of direct laser interference patterning. Using a four-beam interference configuration, hole-like periodic arrays are produced on stainless steel with a 70 ps pulsed laser source operating at 532 nm laser wavelength. The laser processing parameters are optimised for obtaining patterns with the highest possible diffraction efficiency and thus showing the highest possible colour intensity. A model for calculating the required spatial period to obtain a defined colour under specific conditions of illumination and observation angles is presented. A very good agreement between the captured structural colour spectrum and the real visible spectrum of light was obtained. In addition, a strategy for mixing holographic colours, in particular for obtaining the white colour is developed. Finally, the developed model is successfully integrated into machine software, in order to automatically process images that exhibit required colours at certain viewing conditions. The produced patterns are characterised using confocal microscopy and the efficiency of the first diffraction order was measured by optical spectroscopy.